2017
DOI: 10.1590/2177-9465-ean-2016-0347
|View full text |Cite
|
Sign up to set email alerts
|

Institutional links to cope with school violence: an exploratory study

Abstract: Objective: Identify and analyze the institutional links of secondary schools to cope with school violence. Methods: Qualitative, descriptive and exploratory study, based on the concept of social network. Twelve secondary school administrators and coordinators were interviewed. The links established between the schools and other institutions were mapped using minimum maps of social institutional external network and semi-structured interviews. Data were analyzed through thematic content analysis. Results: The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 9 publications
0
7
0
2
Order By: Relevance
“…In a study about the meanings attributed to violence in the school context by teachers, they emphasized the importance of work and a directed look at the family, given the relevance of this institution to the formation and behavior of children and adolescents in other social environments 31 . Despite this importance, the literature corroborates that family-school integration is still a challenge 20 , 31 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study about the meanings attributed to violence in the school context by teachers, they emphasized the importance of work and a directed look at the family, given the relevance of this institution to the formation and behavior of children and adolescents in other social environments 31 . Despite this importance, the literature corroborates that family-school integration is still a challenge 20 , 31 .…”
Section: Discussionmentioning
confidence: 99%
“…In spite of the diversification of the prevalence of violence in the school context, these studies highlight common central issues: school space is not immune to the presence of violence, and adolescents’ exposure to school violence is a worldwide concern that has led researchers from several areas of knowledge to investigate the occurrence of this phenomenon, such as health and education. A recent study addressing this theme identified the fragility or absence of institutional links to address school violence, given the need to think about this problem in an expanded and articulated network 20 .…”
Section: Discussionmentioning
confidence: 99%
“…5 Nursing needs to be sensitive, capable and act in a coordinated way to other services and longitudinal in caring for children and adolescents to host and cope with the situations of violence to which this population is exposed. 23,24 In this context of seeking help and support, the family and school are the places of greatest coexistence and could have the best strategies to confront and/or prevent teenage violence. Literature review highlighted the risk and protective factors for the perpetration of violence in intimate relationships among adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…A categoria docente é uma das mais expostas a ambientes conflituosos e de alta exigência de trabalho, com problemas com alunos que chegam até as ameaças verbais e físicas (FERRIANI,et al, 2017).…”
Section: Introductionunclassified